Aperfeiçoamento da política pública penal no Brasil: a inserção da audiência de custódia no processo penal - Bonatti, Daniel L. (2014)
This study will explore the challenging implementation of policy reforms, focusing the change in the Brazilian Code of Criminal Procedure. The debate refers to the feasibility of adding the detention hearing - right after the arrestment of an individual, allowing the contact between the judge and the arrested person. The Institute for the Defense of the Right to Defense – IDDD proclaims as results of this reform (1) the enhancement of prevention mechanisms and (2) the fight against torture, as well as (3) the effective control of prisons from the Judiciary branch. In addition to this argument, IDDD also plays, not only an influent position as a pressure group, a protagonist role for the criminal code change, through the implementation of the detention hearing.